Multi-omics joint analysis reveals the mechanism of flower color and fragrance variation in Lilium cernuum - Chen, Shaopeng; Chen, Zhiqun; Zhuang, Qianqian; Chen, Hewen (Frontiers in Plant Science, 2025)
IntroductionLilium cernuum, a fragrant purple-red wild lily endemic to Northeast Asia, represents both ecological significance (as a key protected species) and horticultural value. While its white variant (L. cernuum var. album) exhibits distinct flower color and fragrance traits, the molecular mechanisms underlying these variations remain poorly understood. Previous studies attributed the low anthocyanin content in the white variant to LcMYB12 downregulation, yet comprehensive analyses of associated genes and metabolic pathways are lacking.MethodsThis study employed integrated transcriptomics, metabolomics, and volatile metabolomics to systematically compare L. cernuum and its white variant. We analyzed differential gene expression in the phenylpropanoid and flavonoid biosynthesis pathways, quantified anthocyanin/flavonoid metabolites, and assessed volatile organic compound profiles.ResultsThe white variant showed significant reductions in flavonoids (catechin, epicatechin) and anthocyanins (cyanidin, pelargonidin, peonidin), linked to the downregulation of 58 genes in the flavonoid pathway—including PAL, C4H, 4CL, and UFGT. Critically, UFGT suppression disrupted anthocyanin glycosylation, promoting degradation and vacuolar accumulation failure. Concurrently, phenylpropanoid pathway inhibition reduced p-coumaric acid synthesis, diminishing downstream anthocyanins and volatile compounds (eugenol/methyleugenol).DiscussionOur multi-omics approach reveals that flower color loss in L. cernuum var. album results from synergistic effects of transcriptional regulation and metabolic flux redirection. The UFGT-mediated glycosylation defect provides a novel explanation for anthocyanin instability in white petals. These findings complement prior genetic studies and establish a framework for targeted breeding of ornamental traits in Lilium species.